Maximum dose sacubitril/valsartan in heart failure with reduced ejection fraction: does atrial fibrillation compromise the benefits?. (3rd October 2022) - Monteiro, E; Barbosa, J; Guimaraes, J; Fernandes, D; Costa, G; Gomes, R; Rosa, J; Campos, G; Costa, S; Baptista, R; Franco, F; Madeira, M; et al.
Abstract: Background: In the PARADIGM-HF trial, sacubitril/valsartan (SV) was shown to be superior to enalapril in reducing hospitalizations for worsening heart failure (HF), cardiovascular mortality, and all-cause mortality in patients with heart failure with reduced ejection fraction (HFrEF). The 2021 ESC Guidelines recommends SV as a replacement for angiotensin-converting-enzyme inhibitors to reduce the risk of HF hospitalization and death. There is little information regarding the effects of SV according to atrial fibrillation (AF) status. Purpose: The aim of this study was to compare the effects of maximum dose SV regarding symptomatic improvement, change in natriuretic peptides levels (NP) and left ventricular ejection fraction (LVEF) in patients with HFrEF with and without AF. Methods: Retrospective analysis of 137 patients with HFrEF on maximum dose SV (97/103mg twice daily). Patients were divided into two groups according to AF status. Age, gender, relevant comorbidities, usual medication, baseline symptomatic status, NP levels and LVEF were assessed using the Mann-Whitney U or χ 2 test (according to variable type) to ensure comparability between groups. Variation in NYHA class, NP levels and LVEF between baseline and 6-month follow-up was evaluated and compared between groups. Results: Comparison between groups is presented in Table 1. In our studied population, ischemic aetiology was more common in the sinus rhythm group (49.5% vs 30.4%; p 0.034). There were no significant differences between groups regarding age, gender, hypertension, diabetes, and beta-blocker and mineralocorticoid receptor antagonist usage. At baseline, the AF group had higher NT-proBNP levels [median 1421 mg/dL (IQR 743–3087) vs 467 mg/dL (IQR 140–797); p<0.001]. There were no significant differences regarding baseline NYHA class or LVEF. After 6 months of follow-up, reductions in NYHA class [−1 (IQR −2, −1) for AF; −1 (IQR −1, 0) for SR; p=0.437] and NT-proBNP levels [−358 mg/dL (IQR −2275, −47) for AF; −162 mg/dL (IQR −364, 27) for SR; p=0.156], as well as LVEF improvement [11% (IQR 3–15) for AF; 12% (IQR 7–21) for SR; p=0.201], displayed no statistically significant differences between the two groups. Conclusions: Our study shows that the beneficial effects of SV on symptomatic status, NP levels and LVEF were not compromised by the presence of AF at baseline. Funding Acknowledgement: Type of funding sources: None.